Flexible, stretchable and weavable piezoelectric fiber1. Issue 9 (6th February 2015) - Sim, Hyeon Jun; Choi, Changsoon; Lee, Chang Jun; Kim, Youn Tae; Spinks, Geoffrey M.; Lima, Marcio D.; Baughman, Ray H.; Kim, Seon Jeong
<x xml:space="preserve">Abstract</x> The flexible piezoelectric fibers can be stretched to a tensile strain of 5% and can generate over 50 μW·cm−3.The FPFs are sufficiently robust for knotting, sewing and weaving and can also be converting to piezoelectric coils by twist insertion. These spring‐like coils can be reversibly stretched to 50% strain without failure.